OD WIEDZY INSTYTUCJI DO WIEDZY TERENU - W STRONĘ DEMOKRATYCZNEGO WYTWARZANIA WIEDZY NA TEMAT KOBIET ŚWIADCZĄCYCH USŁUGI SEKSUALNE - Dziuban, Agata; Ratecka, Anna (Studia humanistyczne AGH (Kraków), 2012)
In our article we critically examine institutionalized forms of knowledge concerning female sex workers. Re-ferring to our knowledge gathered during field work concerning situation of female sex workers in Poland and experiences as streetworkers associated with non-governmental organization, we have distinguished two disparate kinds of knowledge concerning female sex workers. On the one hand, we have identified "institutional knowledge", exterior to them and created without their participation by the academic institutions, enforcement agencies (the police, prosecution) and aid institutions (governmental and non-governmental), and - on the other hand - "field knowledge", constructed in a dialogue with female sex workers in the process of social work, particularly streetwork. The main difference between those two types of knowledge lies in the power relations intrinsic to the process of knowledge production, interests realized through this process and actions undertaken as its consequence.